The Phenomenology of Socio-Cultural Practices of the Digital Noosphere - Девтеров, І. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The article invites to have a broader look at the phenomenon of socio-cultural practices in the digital noosphere, suggesting a cross-disciplinary approach to the study of the cybersocium in general and the personality in particular, that has been formed during recent years. The humanitarian and technical basis of this methodology, which necessity is dictated by the object of the study, is based on the consideration of the discrete-continuum duality of the digital noosphere. The complexity and diversity of social manifestations of this reality, described in the study, suggest the complexity and diversity of methodological approaches constructed to harmonize two mutually exclusive processes based on the "first" and "second" nature. The aim of this article is to analyze the essence of the phenomenon of socio-cultural practices in the digital noosphere, which inevitably and naturally leads to the need for the synthesis of discrete and continuous ways of comprehending reality, known to the scientific and philosophical tradition, on the basis of the dialectical method of cognition. Research methods used in this article suggest using the opposite sides of reality as system models of the object under study. Like is proposed to study like, and vice versa. Ways of studying different aspects of cybersocial reality can only partially be traditional, despite their methodological reliability. As a research result, it was found that the discrete-continuum duality of the digital noosphere is inherent in its very nature, as is the corpuscular-wave dualism in the physical nature of light. Various positive and negative aspects of human intelligence functioning in the digital noosphere are considered too. Comparative analysis of control systems based on artificial intelligence and traditional social reality leads to inevitable conclusions about the need for more detailed approaches to cyberadaptation of Homo Cyberus (Pleshakov V., 11) as an active participant in cybersocial processes. Discussion says that the differences in the two worlds (electronic-digital and subject-material) are quite obvious to us. The digital world has absorbed many properties of the ideal world, because it is projective, changeable at our will, but existing objectively and independently of our consciousness at the same time. The experience of digital socio-cultural practices tells us that this environment is quite favorable for the formation of the subject field of new scientific disciplines, for the formation and approval of new types of art as ways of self-realization of the personality of everyone, fully included in the digital noosphere. Conclusions. As you know, social progress always has two sides. In the case of the formation of the extremely formalized environment, which is discussed in this article, we observe both positive and negative trends. This is expressed in the desire to ensure the coadaptation of two natural antipodes - human and artificial intelligence. Their main difference is, first, in their origin, and, secondly, in the ways of solving problems of any complexity. Algorithmic and mathematical, that is, the discrete nature of artificial intelligence come into conflict with the intuitiveness, emotionality and spirituality of human intelligence. Thus, the ideas of transhumanism, in the form and context in which they are preached, need correction. Renaissance 2.0 (neuro-digital) can take place only if the classical traditions of anthropocentrism are observed. This will ensure real and not imaginary social progress in the 21st century.